Perencanaan Jalur Hijau Kota Wisata Cibubur Berbasis Prediksi Kapasitas Serapan NO2 Melalui Analisis Menggunakan Software CITYgreen - Khanh Rizky Ramadhani Wibowo; Bambang Sulistyantara (http://arl.faperta.ipb.ac.id/, 2023)
Emissions can have a negative impact on the Environment and Health. Compounds which can harm human health are sulfur oxides (SOx) nitrogen oxides (NOx), carbon oxides (COx), hydrocarbons (HC), heavy metals (Pb) and particulates. These compounds can have bad effects in a densely populated area such as in a housing complex.. This study aims to determine plant species along the main road of Kota Wisata Cibubur, predict the amount of emissions in Kota Wisata Cibubur’s main roads, and to give a planting recommendation which can decrease NO2 emission. The benefit of this research is as a recommendation to the real estate company to give more benefits for the residents in the housing estate in terms of planting the types of plant which can absorb NO2 emission. The research method used is descriptive quantitative method in which the planning process for this research consists of objectives, inventory, analysis, synthesis, and planning. The highest NO2 emission recorded was 85,119.91 kg/year. Emissions absorbed is still not sufficient emough despite after adding plants to the available open green spaces. Therefore, it is necessary to add plants in a radius of 500 m from the main road because NO2 emissions can have an impact on health in a radius of 500 m. Along the radius, there are varieties of ground covers which are garden, built areas, streets, open areas, and moor. The concept for planting in each ground covers will vary. Just like the planting recommendation in the main access road, the plants used will be according to the standard of the plants which can optimally absorb NO2. Plants which are suitable to absorb NO2 emissions and are mostly used are dadap (Erythrina variegata), Ki Hujan (Samanea saman), ylang-ylang (Cananga odorata), and Flamboyant (Delonix regia).